La promoción de la salud y la nueva práctica de la salud pública (1996)
ABSTRACT: This article addresses the framework of the strategy of Health Promotion, also called by some authors and public health professionals as "the new public health". Some of the evolve from the concepts and the principles of the strategy, mechanisms of implementation, and instruments that have been developed during recent years to use in public health are discussed. Emphasis is made on the five areas of action proposed in the Letter of Ottawa and the places of the world where Health Promotion programs have been implemented.